2020
DOI: 10.1080/25787489.2020.1794439
|View full text |Cite
|
Sign up to set email alerts
|

Pooled resistance analyses of darunavir once-daily regimens and formulations across 10 clinical studies of treatment-naïve and treatment-experienced patients with human immunodeficiency virus-1 infection

Abstract: (2020) Pooled resistance analyses of darunavir once-daily regimens and formulations across 10 clinical studies of treatment-naïve and treatment-experienced patients with human immunodeficiency virus-1 infection,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…These results are consistent with those from other darunavir-based studies, in which patients were able to achieve virologic response despite harboring baseline NNRTI and/or N(t)RTI resistance-associated mutations. 28 There are limited clinical trial data regarding the initiation of ART in acute or early HIV-1 infection. 1 However, in a retrospective case-note analysis of 113 patients in the United Kingdom diagnosed with acute HIV-1 infection, the time from diagnosis to ART initiation was 20 days (median), and high rates of virologic suppression were observed.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with those from other darunavir-based studies, in which patients were able to achieve virologic response despite harboring baseline NNRTI and/or N(t)RTI resistance-associated mutations. 28 There are limited clinical trial data regarding the initiation of ART in acute or early HIV-1 infection. 1 However, in a retrospective case-note analysis of 113 patients in the United Kingdom diagnosed with acute HIV-1 infection, the time from diagnosis to ART initiation was 20 days (median), and high rates of virologic suppression were observed.…”
Section: Discussionmentioning
confidence: 99%
“…64 There are only very rare cases of treatment-emergent resistance in clinical trials of boosted DRV-based regimens in treatmentnaive and virologically suppressed treatment-experienced PLWH, with slightly more cases in individuals who were treatment-experienced and had active viral replication at study entry. 12 Virologic failure while receiving DRV-based regimens usually requires multiple PI DRMs and DRV-specific DRMs, such as V32I, I84V, I54L/M, I50V and L76V. 64 Compared with INSTIs and PIs, treatment-emergent resistance is more common for NRTIs, which are frequently used as the backbone of contemporary treatment regimens.…”
Section: Patterns Of Drug Resistance To Contemporary Artmentioning
confidence: 99%
“…3,4 Despite this, drug resistance to contemporary antiretrovirals has been demonstrated in vitro and is evident, although in small numbers, in clinical trials and real-world settings. [5][6][7][8][9][10][11][12][13][14][15] Drug resistance is likely to reduce ART options and so reduce the likelihood of achieving virologic suppression. If virologic failure is not managed appropriately, HIV can become more resistant and lead to deterioration of the immune system and the development of clinical sequelae (AIDS and non-AIDS morbidities), with a continued risk of onward transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in the potency and resistance barrier of antiretroviral drugs for HIV infection, as well as evidence from recent randomized clinical trials (RCTs) in people living with HIV (PLWH), support the use of dual therapy including a boosted protease inhibitor (PI) or a second-generation integrase strand transfer inhibitor (INSTI) in specific patient populations such as PLWH on suppressive antiretroviral therapy (ART) without a history of virologic failure or -at least for some combinations -treatment-naïve PLWH [1][2][3][4]. Both the 2 nd generation INSTI dolutegravir (DTG) and the PI darunavir (DRV, boosted with ritonavir or cobicistat) have been shown to be potent antiretroviral drugs with a high resistance barrier in treatment-naïve and treatmentexperienced PLWH [5][6][7][8]. The DUALIS study (Eudra-CT 2015-000360-34), a phase IIIb, open-label 48-week RCT in virologically suppressed PLWH, demonstrated that switching to a 2-drug regimen (2DR) consisting of boosted DRV (bDRV) plus DTG was non-inferior to continuing a 3-drug regimen (3DR) including bDRV plus two nucleoside/nucleotide reverse-transcriptase inhibitors (NRTIs).…”
Section: Introductionmentioning
confidence: 99%